Correlative Analysis of the Dimensional Properties of Bipyramidal Titania Nanoparticles by Complementing Electron Microscopy with Other Methods - Loïc Crouzier; Nicolas Feltin; Alexandra Delvallée; Francesco Pellegrino; Valter Maurino; Grzegorz Cios; Tomasz Tokarski; Christoph Salzmann; Jérôme Deumer; Christian Gollwitzer; Vasile-Dan Hodoroaba (Nanomaterials, 2021)
In this paper, the accurate determination of the size and size distribution of bipyramidal anatase nanoparticles (NPs) after deposition as single particles on a silicon substrate by correlative Scanning Electron Microscopy (SEM) with Atomic Force Microscopy (AFM) analysis is described as a new measurement procedure for metrological purposes. The knowledge of the exact orientation of the NPs is a crucial step in extracting the real 3D dimensions of the particles. Two approaches are proposed to determine the geometrical orientation of individual nano-bipyramides: (i) AFM profiling along the long bipyramid axis and (ii) stage tilting followed by SEM imaging. Furthermore, a recently developed method, Transmission Kikuchi Diffraction (TKD), which needs preparation of the crystalline NPs on electron-transparent substrates such as TEM grids, has been tested with respect to its capability of identifying the geometrical orientation of the individual NPs. With the NPs prepared homogeneously on a TEM grid, the transmission mode in a SEM, i.e., STEM-in-SEM (or T-SEM), can be also applied to extract accurate projection dimensions of the nanoparticles from the same sample area as that analysed by SEM, TKD and possibly AFM. Finally, Small Angle X-ray Scattering (SAXS) can be used as an ensemble technique able to measure the NPs in liquid suspension and, with ab-initio knowledge of the NP shape from the descriptive imaging techniques, to provide traceable NP size distribution and particle concentration.